The surgical ablation on soft tissues using Ho:YAG laser with deviated beam fiber - Jaafar, Nurul Syahirah Aziz; Lim, Kok Sing; Zaini, Muhammad Khairol Annuar; Ahmad, Harith; Sepeai, Suhaila; Tan, Guan Hee; Tan, Geok Chin; Zainuddin, Zulkifli Md. (Elsevier, 2019)
In this work, we demonstrate the use of 2.12-μm Ho:YAG laser with a deviated-firing fiber for laser ablation on chicken tissues. The tissue ablation tests were conducted under non-contact and contact conditions. The thermal damage and ablation efficiency made by the fiber on the tissue were quantitatively analyzed and compared. It is found that, the ablation threshold is lower and ablation is more efficient under the non-contact mode, in which the fiber device is kept at a small distance of 0.5–1.0 mm from the target tissue. This can be attributed to amber space between the fiber and the tissue that allows the ejection of ablation debris and vapor from the ablation zone. This ensures better transmission of laser energy from the fiber device to the target tissue. Such design offers better ablation efficient and enhances the service life of the medical fiber device. © 2019 Elsevier Inc.